2018
DOI: 10.3892/ol.2018.9850
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of matrix metalloproteinase‑9 predicts papillary thyroid carcinoma prognosis

Abstract: The present study aimed to explore the association between immunohistochemical matrix metalloproteinase-9 (MMP-9) expression and the clinicopathological characteristics of patients with papillary thyroid carcinoma (PTC), and to determine whether it may be used as a diagnostic or prognostic tool for PTC. Immunohistochemical staining of MMP-9 was performed in thyroid tissues obtained from 112 patients with PTC and 42 subjects with benign thyroid nodules (BTNs). The receiver operating characteristic curve was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
(51 reference statements)
2
25
0
1
Order By: Relevance
“…The result of this study was consistent with a study by Liu et al [23] which also found a significant correlation between MMP-9 expression and central and lateral lymph node metastasis in the late-stage PTC (stage III-IV) (p < 0.05). A study by Hwang et al [24] investigating MMP-9 in gastric cancer, also reported a similar result where MMP-9 was correlated with lymph node metastasis and lymphatic invasion, and bad prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The result of this study was consistent with a study by Liu et al [23] which also found a significant correlation between MMP-9 expression and central and lateral lymph node metastasis in the late-stage PTC (stage III-IV) (p < 0.05). A study by Hwang et al [24] investigating MMP-9 in gastric cancer, also reported a similar result where MMP-9 was correlated with lymph node metastasis and lymphatic invasion, and bad prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown MMP-9 to have good sensitivity and specificity for the diagnosis of PTC [23].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous researches have highlighted the particular association of MMP‐1, MMP‐2 and MMP‐9 with local invasiveness, angiogenesis and metastatic potential of certain malignant tumours . Generally, studies that investigate expressions of MMPs and TIMPs in PTC are focused mainly on differentiating malignant from benign thyroid nodules . The present study is focused exclusively on metastatic PTC and is investigating differences in expression among certain metastatic groups.…”
Section: Discussionmentioning
confidence: 95%
“…7,13 Generally, studies that investigate expressions of MMPs and TIMPs in PTC are focused mainly on differentiating malignant from benign thyroid nodules. 14 The present study is focused exclusively on metastatic PTC and is investigating differences in expression among certain metastatic groups.…”
Section: Discussionmentioning
confidence: 99%